Detection of Flavonoids from Jatropha gossypiifolia L. var. Elegans Muell. Arg. - Ladda3; G.M.Rathod4, V. T. Narwade1*, A. A. Waghmare2, R.G. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;">Flavonoids from Jatropha gossypiifolia L. var. elegans Muell. Arg were extracted by using different solvent and they were identified and detected by Thin Layer Chromatography (TLC) and spectroscopic method. Flavonoids like anthocyanidins, glycosides, flavonols and flavones were detected from Jatropha gossypiifolia L. var. elegans Muell. Arg.<span style="line-height: 110%; font-family: ";Times New Roman";,";serif";; font-size: 10.5pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-size: 10.0pt;"> <span style="line-height: 110%; font-family: ";Times New Roman";,";serif";; font-size: 10.5pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-size: 10.0pt;">— <span style="line-height: 110%; font-family: ";Times New Roman";,";serif";; font-size: 10.5pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-size: 10.0pt;"> 1Bahirji Smarak Mahavidyalaya, Basmathnagar Dist. Hingoli (M.S.), India 2Sidharth College, Jafrabad Dist.Aurangabad (M.S.), India 3S.J.College, Gangakhed Dist. Parbhani (M.S.), India 4S.K.M., Gunjoti, (M.S.), IndiaÂ Â — Please Cite This Article As: Â V. T. Narwade1*, A. A. Waghmare2, R.G.Ladda3 and G.M.Rathod. 2010. Detection of Flavonoids from Jatropha gossypiifolia L. var. Elegans Muell. Arg. J. Ecobiotechnol. 2(6):14-16. Â